Health Status of Nonemergency Patients in the Emergency Department Using the EQ-5D - Min Dai; Jingyuan Jiang; Lingjun Jiang; Jin Zhou; Lei Ye (Emergency Medicine International)
Background. Emergency department (ED) overcrowding is influenced by several factors including the hospital’s capacity, staff, patient discharges, and community resources. The number of annual ED visits has increased, with patients’ medical needs exceeding emergency capacity, resulting in a widespread concern about emergency room overcrowding. Nonemergency patients tend to use large amounts of emergency medical resources, which is one reason for ED overcrowding. Most patients consider their medical cases urgent, whereas medical professionals consider many cases to be nonemergency. Only a few studies have examined self-rated health among nonemergency patients. Methods. This cross-sectional study was conducted in the ED of a tertiary hospital in China using the European Quality of Life Five-Dimensional Questionnaire to investigate the health status of nonemergency patients. Results. Among the 545 respondents, 246 (45.14%) self-assessed their health as excellent, 186 (34.13%) as very good, 70 (12.84%) as good, 32 (5.87%) as average, and 11 (2.02%) as poor. Problems related to pain/discomfort were reported by 317 (58.17%) participants, 214 (39.27%) responded that they had problems related to daily activities, 212 (38.90%) responded that they felt anxious or depressed, 211 (38.35%) responded that they had problems related to self-care, and some or extreme problems related to mobility were stated by 193 people (35.41%). Conclusions. Nonemergency patients generally reported good health. Pain/discomfort was the most significant factor affecting the health of nonemergency patients, followed by limitation of daily activities. The duration of illness onset and self-rated health status were common factors influencing the health status of nonemergency patients. This trial is registered with ChiCTR1900023578.